Outcomes and Associated Factors of Cataract Surgery Among Adults Attending a Tertiary Hospital in Addis Ababa, Ethiopia - Markos, Cherinet M (Patient Relat Outcome Meas, 2020)
BACKGROUND: Visual outcomes and factors associated with cataract surgery vary from country to country and within countries. This study aimed to evaluate associated factors and visual outcomes following cataract surgery among adults attending Saint Paul’s Hospital Millennium Medical College (SPHMMC), Addis Ababa, Ethiopia. PATIENTS AND METHODS: We conducted a prospective, longitudinal study of consecutive adult patients scheduled for cataract surgery between May 2018 and April 2019. Preoperative, intraoperative and postoperative data were collected and analyzed using SPSS version 23.0. Descriptive statistics and binary logistic regressions were used to analyze the data. We used World Health Organization (WHO) criteria for cataract surgery outcome assessment as a reference for comparison. RESULTS: Three hundred fourteen eyes of 314 participants (mean age 64.16±8.83 SD, 52% females, 44% from rural location) were included in the study. Most, 283 (90.1%) had preoperative visual acuity less than 6/60. At final follow-up visit (6 to 8 weeks), best-corrected visual acuity (BCVA) was good (≥6/18) in 215 (68.5%), borderline (<6/18–6/60) in 63 (20.1%) and poor (<6/60) in 36 (11.5%) eyes. Age-related macular degeneration (AMD) [OR = 4.57, 95% CI [1.12–17.24], p=0.03] and preoperative astigmatism [OR = 3.22, 95% CI [1.25–8.33], p=0.01] were significantly associated with poor postoperative visual outcome. CONCLUSION: While the majority of patients had good postoperative BCVA following cataract surgery, the percentage of patients with poor visual outcomes was higher than the WHO standard. Greater attention to pre-existing co-morbidities such as retinal disease and high astigmatism could improve outcomes by optimizing patient selection and surgical approach.